2016
DOI: 10.3386/w22885
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth and Carbon Emissions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The larger the population, the more activities people carry out both distribution and consumption production which ultimately increases CO 2 emissions released. Furthermore, research conducted by Casey and Galor (2018) implied that a population growth of 1% slower can be accompanied by an increase in per capita income of almost 7% while being able to reduce carbon emissions. If the population continues to grow which results in continuous fertilization of carbon emissions, then it increases climate change with the risk of forest fires by the end of 2020 (Knorr et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The larger the population, the more activities people carry out both distribution and consumption production which ultimately increases CO 2 emissions released. Furthermore, research conducted by Casey and Galor (2018) implied that a population growth of 1% slower can be accompanied by an increase in per capita income of almost 7% while being able to reduce carbon emissions. If the population continues to grow which results in continuous fertilization of carbon emissions, then it increases climate change with the risk of forest fires by the end of 2020 (Knorr et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…While a few studies examine global emission changes using large data (Pani and Mukhopadhyay, 2010), most studies are based on country-level or regional data. Some studies emphasized population as the main factor of emission (Casey and Galor, 2016), while some underlined income as the major driver (Hang and Yuan-sheng, 2011). The environmental Kuznets curve (EKC) proposes an inverted U-shaped relation between economic growth and environmental deterioration (Yandle et al, 2007).…”
Section: A Survey Of Literaturementioning
confidence: 99%
“…Byrch et al [46] have found the participant maps in promoting business, and accommodating economic growth and development, as the key player in the sustainable development after they revisited the meaning of sustainable development held by New Zealand. In addition, Casey and Galor [47] examined the carbon emissions in terms of their effect of lower fertility. Regardless of its complexity, population policies were found to be part of the approach to tackling global climate change.…”
Section: Literature Reviewmentioning
confidence: 99%